Pluronics modified liposomes for curcumin encapsulation: Sustained release, stability and bioaccessibility - Li, Zi-ling; Peng, Sheng-feng; Chen, Xing; Zhu, Yu-qing; Zou, Li-qiang; Liu, Wei; Liu, Cheng-mei (Food research international, 2018)
The present work evaluated the feasibility of different pluronics (F127, F87 and P85) utilized as modifiers to improve the stability and bioaccessibility of curcumin liposomes (cur-Lps). Pluronics modified curcumin liposomes (cur-pluronic-Lps) were prepared by thin film evaporation combined with dynamic high pressure microfluidization. The particle size and polydispersity index of cur-pluronic-Lps was significantly lower than cur-Lps. Fourier transform infrared spectroscopy analysis revealed that curcumin was loaded in liposomes successfully and X-ray diffraction suggested that curcumin in the liposomes was in an amorphous state. In vitro release studies demonstrated that 73.4%, 63.9%, 66.7% and 58.9% curcumin released from cur-Lps, cur-F127-Lps, cur-F87-Lps and cur-P85-Lps, respectively. Compared with cur-Lps, cur-pluronic-Lps showed a slower release rate and lower cumulative release percentage for curcumin. Non-Fickian transport was the main release mechanism for cur-Lps, cur-F127-Lps and cur-F87-Lps, and typically the first-order model fitted cur-P85-Lps release. Stability studies (exposure to solutions of different pH and heat treatment) indicated that pluronics modification could enhance their pH stability and thermal stability. In vitro simulated gastrointestinal tract studies suggested that pluronics modification could significantly improve the absorption of cur-Lps. Bioaccessibility of curcumin liposomes increased in the following order: cur-Lps < cur-F87-Lps < cur-P85-Lps < cur-F127-Lps. These results may guide the potential application of pluronics modified liposomes as carriers of curcumin in nutraceutical and functional foods. [Display omitted] •Novel pluronics modified liposomes were prepared for curcumin encapsulation.•Pluronic modified curcumin liposomes showed sustained release.•Pluronics modified curcumin liposomes demonstrated improved thermal and pH stability.•Curcumin loaded in Pluronics modified liposomes possessed increased bioaccessibility.